Impact of microcin J25 on the porcine microbiome in a continuous culture model - Naimi, Sabrine; Zirah, Séverine; Greppi, Anna; Lacroix, Christophe; Rebuffat, Sylvie; Fliss, Ismail (Frontiers in Microbiology, 2022)
The increased prevalence of Salmonella spp. resistance in swine spurs the search for alternatives to antibiotics. Microcin J25 (MccJ25), a bacteriocin produced by Escherichia coli, is a potent inhibitor of several pathogenic bacteria including Salmonella enterica. In this study, we aimed to evaluate in vitro the impact of MccJ25 on the composition and the metabolic activity of the swine colonic microbiota. The PolyFermS in vitro continuous fermentation model was used here with modified Macfarlane medium to simulate the porcine proximal colon. During 35 days of fermentation, a first-stage reactor containing immobilized swine fecal microbiota fed two second-stage control and test reactors operated in parallel and used to test the effects of MccJ25 on the composition and the metabolic activity of the microbiota. Reuterin, a broad-spectrum antimicrobial compound produced by Limosilactobacillus reuteri, a lactic acid bacterium naturally present in the gastro-intestinal tract of human and animals, and the antibiotic rifampicin were tested for comparison. Sequencing of 16S rRNA was performed using the Illumina MiSeq technology to evaluate microbial diversity, and liquid chromatography coupled to mass spectrometry (LC-MS) followed by multivariate analysis was used to assess the bacteriocin/antibiotic degradation products and monitor changes in the swine colonic microbiota metabolome. The results show that MccJ25 or reuterin treatments only induce subtle changes of both the microbial diversity and the metabolome of the swine colon microbiota, while rifampicin induces significant modification in amino acid levels. Although these finding needs being validated in vivo, our results suggest that MccJ25 could be a possible alternative to antibiotics for veterinary and farming applications.